English Language - Fikri Haekal Amdar (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
Muhammad Yasin al-Fadani as a Nusantara cleric through the book Al-Arba'un Haditsan min Arba'in Kitaban 'an Arba'ina Shaykhan, has contributed to the study of hadith. The aims of this research are: first, to discuss the biography of Sheikh Yasin al-Fadani. Second, discussing the scientific journey of knowledge, looking for his sanad. Third, how is the process of compiling the book Al-Arba'un Haditsan min Arba'in Kitaban 'an Arba'ina Shaykhan. Fourth, the hadith of the curse of Muawiyah and the syarah of Sheikh Yasin al-Fadani in the book of Al-Arba'un Hadith min Arba'in Kitaban 'an Arba'ina Shaykhan. This type of research is library research sourced from articles and books related to the discussion about Sheikh Yasin al-Fadani and refers directly to the book of hadith written by Sheikh Yasin al-Fadani. This study concludes that in the view of Sheikh Yasin al-Fadani that the hadith allegedly containing curses to Muawiyah must be understood as part of the Arab tradition, so it is not understood that the Prophet intended to curse Muawiyah.